Associations between prenatal exposure to fine particulate matter and birth weight and modifying effects of birth order related to a new baby boom: A prospective birth cohort study in Guangzhou, China. (15th June 2020) - Dong, Moran; Liu, Xin; Xiao, Jianpeng; Sun, Xiaoli; Ye, Yufeng; Feng, Baixiang; Zeng, Weilin; Hu, Jianxiong; Li, Xing; Guo, Lingchuan; Rong, Zuhua; Sun, Jiufeng; et al.
Abstract: Although studies have assessed the associations between prenatal exposure with fine particulate matter (PM) with birth weight, few have investigated the effect of PM1 exposure and identified the susceptible exposure window. Additionally, a baby boom occurred after China implemented the universal two-child policy, but whether the effects of PM are modified by birth order remains unknown. The objective of this study was to estimate the effects of prenatal exposure to PM (PM2.5 and PM1 ) on birth weight, identify the susceptible exposure windows, and assess the modifying effect of birth order on the effects of PM exposure. All participants were selected from the Prenatal Environment and Offspring Health (PEOH) cohort conducted since 2016 in Guangzhou, China. A spatiotemporal land–use-regression (STLUR) model was used to estimate a pregnant woman's weekly PM2.5 exposure, and a generalized additive model (GAM) was used to estimate each PM1 exposure. A distributed lag non-linear model (DLNM) was applied to assess the exposure–lag-response associations between weekly PM exposure and birth weight. The sample included 4086 pregnant women. The results showed that maternal exposure to PM2.5 and PM1 during the 15th to 24th and 16th to 24th gestational weeks were associated with lower birth weight, the strongest association was observed in the 19th week, during which each 10 μg/m 3 increment in PM2.5 and PM1 was associated with a 1.47 g (95% CI: 2.49 g, 0.44 g) and 1.58 g (95%CI: 2.74 g, 0.41 g) decrease in birth weight, respectively. Compared with the first-born neonates, greater effects of PM2.5 and PM1 exposure on birth weight were observed among the second-born neonates in the 15th to 21st and 15 h to 22nd gestational weeks. Further studies tracking the health of the second-born children are warranted because they may be more sensitive to environmental factors than the first-born children. Highlights: First to study the modifying effects of birth order on PM exposures and birthweight. Prenatal exposure to higher PM2.5 and PM1 were associated with birth weight loss. PM1 may have a stronger effect on birthweight than PM2.5. The 15th to 24th and 16th to 24th gestational weeks might be the critical windows of PM2.5 and PM1 exposures. PMs had greater effects on the second-born neonates than the first-born neonates.